Estudo da interação do vanádio (V) com ácidos [beta]-alaninoidroxâmico, glicinoidroxâmico e [alfa]-alaninoidroxâmico em solução aquosa $h [manuscrito] : $b uma abordagem a partir da DFT - Isabella Pires Ferreira (2009)
The discovery of the potential insulin-mimetic properties of vanadium compounds has stimulated research about the clinical use of these compounds. The effects of different organic groups in the geometry, electronic structure and chemical properties of the vanadium coordination compounds are of fundamental importance to understand the chemical reactivity and biological activities these compounds. The vanadate [VO2]+ ion interacts with the hydroxamate anion (L¯) forming 1:1 and 1:2 metal/ligand ratio species. The interaction between vanadium (V) and ß-alaninehydroxamic, ghycinehydroxamic and a-alaninehydroxamic acids has been theoretically studied by means of density functional theory (DFT) method using the exchange and correlation potentials PBE and BP86. All different geometric isomers as well as the various tautomers of the complexes formed in the three systems have been investigated.In all species the hydroxamate ligand coordinates to the metallic center forming a five member ring. The most stable optimized structures of species with 1:1 metal:ligand proportion resulted in five-coordinated vanadium(V) oxocomplexes with a distorted trigonal bipiramidal geometry. Complexes containing two ligands per vanadium atomhave hexacoordinated structures and the most stable ones have an oxo group protoned. Deprotonation occur in the nitrogen atoms of the carbonic chains. No great distortions from the octahedral geometry of these species were observed. The most stable isomers are those with the V-O and V-OC bonds in a trans position to each other. Theoretically calculated Gibbs free energy of formation of the complexes wereestimated and compared with experimentally measured values. The hydrolysis free energies of the species have also been estimated. Solvation energy was estimated using the polarizable continuum model (PCM). The average differences between calculated and experimental values were in the order of 5,0 Kcal.mol-1. The 51V NMR isotropic chemical shift diso, of the most stable optimized species ofeach system have been theoretically estimated, with the GIAO method employing the B3LYP functional with different basis sets. Good agreement is observed, with differences between theoretical and experimental shifts in the range of 6-41ppm with B3LYP-631G(d) level of theory. A combination between the 51V NMR experimentalvalues and computational methods is useful for investigation of the electronic structure and geometric environment in vanadium systems.The electronic spectra, for the most stable vanadium compounds, have beenstudied by means of time dependent density functional theory (TD-DFT). The electronic absorption spectra are dominated by ligand-to-vanadium charge transfer (LMCT) transition. Based on the MO scheme of species, the UV-vis transitions were assigned.